Literature Review: Factors Associated with Malnutrition in Children Younger than Five - Fikri Faidul Jihad; Susy Sriwahyuni; Darmawan Darmawan; Lily Eky Nursia N; Ihsan Murdani (Journal of Nutrition Science, 2022)
The lack of healthy sustenance is far-reaching in emerging nations, including Indonesia. Lack of healthy sustenance can restrict a singular's capacity to reach their greatest potential. Factors that impact undernutrition should be recognized to decrease undernutrition rates in little children. This article aims to analyze factors related to undernutrition in children under five years of age. This study uses the literature review method. The database used to search for articles that match the theme is taken from several search engines: Google Scholar and Garuda. Selecting articles is based on suitability with the keywords, topics, and predetermined inclusion and exclusion criteria. The results of this study are ten factors related to malnutrition in toddlers, namely the Mother's knowledge, parenting style, history of exclusive breastfeeding, history of illness, number of family members, child feeding patterns, family economic income status, low birth weight (LBW), Mother's education level, and energy-protein adequacy. The ten factors related to malnutrition in toddlers were obtained from valid scientific evidence using procedures. Thus, this literature review can be a scientific reference to be applied as an intervention for malnutrition in toddlers.